Environmental perturbations and anthropogenic disturbances determine mollusc biodiversity of Africa’s explosive Lake Kivu - (:unkn) unknown (My University, 2024)
Lake Kivu (Rwanda and Democratic Republic of Congo) is known to be unique among the African Great Lakes due to its peculiar history as a volcanic barrier lake and the frequent environmental pertubations caused by limnic eruptions. This lake is a major resource for riparian people but is also characterized by a depauperate fauna. For molluscs, available information is scarce and spatio-temporally restricted. We studied the freshwater molluscs of the lake and its tributaries and their biogeographical affinities, for the first time via genetic characterization. Our study revealed that the malacofauna of Lake Kivu, though admittedly poor compared to other African Great Lakes, is significantly more diverse than previously anticipated. The occurrence of living populations is restricted to a narrow fringe of littoral substrates, but some of the total of eight species occur much deeper than the immediate margins of the lake, i.e. down to a maximum of 15 m. The fauna displays 'Nilotic' biogeographic connections though widespread forms dominate. Differences in diversity occur in the North vs. South of Lake Kivu in species richness and abundance measures. This pattern can be attributed to recent volcanic eruptions and geochemical stressors in the north, but also to current and ongoing anthropogenic effects. A detailed study of schistosomiasis and fasciolosis with high spatial resolution along the local communities and their livestock is recommended since several potential intermediate host snails are present in Lake Kivu and its tributaries.
Keywords: African Research